Sejarah Berdirinya Sekolah Luar Biasa (SLB) Harapan Mulia Kota Jambi 2012 – 20 - Agustin, Yesika; Heidi Karmela, Siti; Agustiningsih, Nur (Universitas Batanghari Jambi, 2023)
The purpose of this research is to describe the history of the development of SLB HarapanMulia Jambi City and to describe the role and contribution of SLB Harapan Mulia for thesociety of Jambi City. The research used historical method starting from the stages ofheuristics, source criticism, interpretation, and historiography. The data sources used primarysources and secondary sources. The primary source was obtained from interviews with theprincipal, teachers and students of SLB Harapan Mulia. Secondary sources in the form ofwritten data are books, articles, documents, and other supporting data. The results showed 1)SLB Harapan Mulia under the auspices of the Education Foundation. Initially, SLB HarapanMulia was a Harapan Mulia Autistic School which was established in 2012 and then developedto provide services to children who have another disabilities, both at the TKLB, SDLB andSMPLB levels. 2) SLB Harapan Mulia as one of the private Special Schools that have a role toproviding education for children with special needs who are not accepted in public schools butthey want to go to school.